GE_GERICHTE P/6822/2018 vom 22. Mai 2018 - GE Cour de justice (2018)
DROIT D'ÊTRE ENTENDU ; ENRICHISSEMENT ILLÉGITIME ; ABUS DE CONFIANCE ; SOUSTRACTION D'UNE CHOSE MOBILIÈRE | CPP.310; CPP.318.al2; CP.137; CP.138.al1.ch1; CP.141